Interprofessional contact with conventional healthcare providers in oncology: a survey among complementary medicine practitioners - Marit Mentink; Julia Jansen; Janneke Noordman; Liesbeth van Vliet; Martine Busch; Sandra van Dulmen (BMC, 2024)
Abstract Background Half of all patients with cancer use complementary medicine. Given the benefits and risks associated with complementary medicine use, contact between complementary medicine practitioners and conventional healthcare providers (oncologists, nurses) is important for monitoring the health and well-being of mutual patients with cancer. Research on occurrence of such interprofessional contact is scarce. This study aims to describe complementary medicine practitioners' experiences with contact with conventional healthcare providers about mutual patients with cancer and the importance they attach to patient disclosure of complementary medicine use to their conventional healthcare provider. Predictors for interprofessional contact are explored. Methods An online survey was administered among complementary medicine practitioners who treat patients with cancer or cancer survivors and who are member of a professional association in the Netherlands. Results The survey was completed by 1481 complementary medicine practitioners. 40% of the participants reported to have contact with conventional healthcare providers of patients with cancer. Only 13% of the complementary medicine practitioners experienced conventional healthcare providers as open to communication with them. An explorative logistic regression showed that openness of conventional healthcare providers as experienced by complementary medicine practitioners was the most important predictor for the occurrence of interprofessional contact (OR = 8.12, 95% CI 5.12-12.86, p < .001). Most complementary medicine practitioners (82%) considered it important that patients disclose complementary medicine use to their conventional healthcare provider and 49% of the participants always motivates their patients to do so. Conclusions Interprofessional contact with conventional healthcare providers in oncology occurs but is not routine for most complementary medicine practitioners. More than one-third of the surveyed complementary medicine practitioners experienced conventional healthcare providers as not open to communication with them. The openness of conventional healthcare providers as experienced by complementary practitioners is an important predictor for interprofessional contact to take place. Most complementary practitioners acknowledge the importance of patient disclosure of complementary medicine use to their conventional healthcare provider. Open communication about the topic of complementary medicine use between complementary practitioners, conventional healthcare providers and patients prevents overlooking relevant medical information and facilitates optimal monitoring of health and safety of patients with cancer.